Contribution of Arbuscular mycorrhizal fungi (AMF), rhizobia and metarhizium anisopliae to cowpea production in Cameroon - Ngakou, A.; Nwaga, D.; Ntonifor, N.N.; Tamo, Manuele; Nebane, C.L.N.; Parh, I.A. (2007)
The objective of this study was to investigate on how the interactions between the microbial syrnbionts (AMF+rhizobia) and the rnycopesticide M. anisopliae can affect the cowpea production in varied agro ecological zones of Cameroon. Cowpea of the Bafia local cultivar was grown from 1999 to 2004 in the Sudano-sahelian (zone-I), Guineasavannah (zone-II), monomodal (zone-IV) and bimodal humid-forest rainfall (zone-V) of Cameroon. Two cropping seasons were experimented in each zone, but in different years except in zone-IV. Experiments were conducted in a Randomised Block Design (RED) with two levels of inoculation at sowing (uninoculanted seeds and dually inoculated seeds with Arbuscular Mycorrhizal Fungi (AMF) and rhizobia and two levels of spray applications at onset of flowering with the mycopesticide (Metarhizium anisopliae), or the insecticide Deltamethrin ®. Results indicate that inoculation significantly increased cowpea biomass in the first and second cropping years, respectively by 38 and 40% in zone-I, 54 and 43% in zone-II, 55 and 46% in zone-IV, 41 and 51 % in zone-Vat 45 Days After Planting (DAP). Inoculated plants showed a low but significant (p = 0.01) response to AMF colonization in all the trials compared to uninoculated plants. Nodules were formed by native and introduced rhizobia while the number and dry weight of nodules were significantly higher (p<0.0 1) in roots of inoculated than those of uninoculated plants. Inoculated and sprayed treatments significantly produced more pods per plant (p<0.01) and enhanced the dry weight of pods per plant at harvest (p = 0.03) in all trials compared to the control. These results suggest that AMF, rhizobia and M. anisopliae are variously efficient microsyrnbionts and mycopesticides in different Cameroonian soils and may be used as economical and safe bio-inoculants to improve cowpea production in the country.